The Lived Experiences of Middle-Aged Couples Engaged in Infidelity: A Grounded Theory Study - Hemadi , Parvaneh; Honarparvaran , Nazanin (Applied Family Therapy Journal (AFTJ), 2025)
Objective: This study aimed to explore and conceptualize the lived experiences of middle-aged couples involved in marital infidelity using a grounded theory approach.Methods and Materials: The research employed grounded theory methodology to systematically analyze the narratives of twelve men and women aged 40–65 years who sought counseling in family consultation centers in Shiraz and who had engaged in infidelity. Participants were selected through purposive sampling until theoretical saturation was achieved. Semi-structured, in-depth interviews served as the primary data collection method, supported by document reviews and field notes. Data analysis followed Strauss and Corbin’s coding procedures—open, axial, and selective coding—with constant comparison and memo writing used to refine categories and develop a coherent theoretical model. Credibility was enhanced through member checking, peer debriefing, and triangulation of perspectives.Findings: The analysis revealed a multi-layered model in which causal conditions such as unmet emotional needs, sexual dissatisfaction, negative spousal behaviors, monotony in marital life, reciprocal betrayal, and situational opportunities fostered extramarital involvement. Contextual factors such as traditional marriages, shifting cultural values, economic stress, low emotional literacy, and family interference further shaped the dynamics. Intervening conditions—including revenge motives, personality traits, spousal neglect, addiction, and social pressures—intensified vulnerability. Participants described a central phenomenon of inner void and dissatisfaction, leading to the search for substitute relationships. Their experiences reflected ambivalence, combining pleasure, novelty, and empowerment with guilt, stress, and anxiety. Strategies centered on secrecy management, deception, and regulation of relationships with third parties. Consequences included divorce, mistrust, emotional detachment, or continuation of hollow marriages, alongside psychological distress, identity disruption, and dependency on the third party.Conclusion: The study highlights the paradoxical duality of infidelity as both a source of excitement and a trigger for guilt and long-term damage, underscoring the need for culturally sensitive interventions in therapy and social support systems.